The pilocarpine model of mesial temporal lobe epilepsy: Over one decade later, with more rodent species and new investigative approaches. (November 2021) - Lévesque, Maxime; Biagini, Giuseppe; de Curtis, Marco; Gnatkovsky, Vadym; Pitsch, Julika; Wang, Siyan; Avoli, Massimo
Highlights: The pilocarpine model is widely used to study temporal lobe epilepsy. Optogenetics and chemogenetics on mutant mice have revealed new information. New data have also been obtained on neuroinflammation, circadian and estrous cycles. New technologies have brought meaningful information on epileptogenesis and ictogenesis. Similar protocols must be used to decreased variability in this model. Abstract: Fundamental work on the mechanisms leading to focal epileptic discharges in mesial temporal lobe epilepsy (MTLE) often rests on the use of rodent models in which an initial status epilepticus (SE) is induced by kainic acid or pilocarpine. In 2008 we reviewed how, following systemic injection of pilocarpine, the main subsequent events are the initial SE, the latent period, and the chronic epileptic state. Up to a decade ago, rats were most often employed and they were frequently analysed only behaviorally. However, the use of transgenic mice has revealed novel information regarding this animal model. Here, we review recent findings showing the existence of specific neuronal events during both latent and chronic states, and how optogenetic activation of specific cell populations modulate spontaneous seizures. We also address neuronal damage induced by pilocarpine treatment, the role of neuroinflammation, and the influence of circadian and estrous cycles. Updating these findings leads us to propose that the rodent pilocarpine model continues to represent a valuable tool for identifying the basic pathophysiology of MTLE.